Religious Moderation as a Paradigm of Moderate Islamic Thought in the Era of Digital Disruption - Puspita W, Dhevin M.Q Agus; Tofaynudin, Johan Indrus; Anwari, M.Syaihul; Dahlan, Moh; Futaqi, Syauqi (Institut Agama Islam Negeri (IAIN) Manado, 2025)
The rapid development of digital technology has fundamentally transformed the religious Muslim societies, particularly in terms of religious authority, the production of Islamic discourse, and modes of da‘wah in digital public spaces. Digital disruption presents both opportunities and serious challenges for the sustainability of moderate Islam, marked by the rise of identity polarization, fragmentation of religious authority, religious hoaxes, and the commodification of religion. This article aims to examine religious moderation as a paradigm of moderate Islamic thought that is relevant in responding to the challenges of the digital disruption era. This study employs a qualitative approach using a library research method by critically analyzing primary and secondary literature related to the concept of wasathiyyah, moderate Islamic thought, and the relationship between religion and digital media. The findings indicate that religious moderation is deeply rooted in Islamic teachings and functions as a theological, epistemological, and social principle that balances text and context, revelation and social reality. In the digital context, religious moderation serves as an ethical and epistemological to safeguard the integrity of religious discourse, counter extremism, and strengthen social cohesion. The article also emphasizes the importance of strengthening religious moderation through digital literacy-based da‘wah, inclusive and argumentative religious narratives, and synergy among academics, religious scholars, and educational institutions. Thus, religious moderation emerges as a strategic paradigm for advancing a civil, balanced, and contextually relevant moderate Islam in the era of digital disruption.